Antiphospholipid antibody levels in early systemic lupus erythematosus: are they associated with subsequent mortality and vascular events?. (30th June 2019) - Pericleous, Charis; D'Souza, Amrita; McDonnell, Thomas; Ripoll, Vera M; Leach, Oliver; Isenberg, David; Giles, Ian; Rahman, Anisur
Abstract: Objectives: aPL are present in between 20 and 30% of patients with SLE. They can cause vascular events (VE) or pregnancy morbidity. aCL and anti-beta-2-glycoprotein I (anti-β2GPI) are measured in clinical practice. Domain I (DI) of β2GPI is the main site for aPL binding. We investigated the prevalence of IgG anti-DI, aCL and anti-β2GPI antibodies in early SLE and their association with mortality and development of VE. Methods: Samples from 501 patients with SLE that had been obtained and stored early during their disease were tested for IgG anti-DI, aCL and anti-β2GPI antibodies by ELISA. LA status and history of VE were obtained by reviewing medical records. Kaplan–Meier analysis was used to investigate mortality and occurrence of VE, comparing groups with and without aPL in early disease. Results: Of 501 patients, 190 (38%) had at least one of these aPL, of whom 112 had anti-DI alone. Of 276 patients with complete vascular history, 83 had experienced VE. The 39 patients who were double or triple-ELISA-positive for any combination of the three aPL were more likely to have or develop lupus anticoagulant ( P <0.0001) than those who were single-ELISA-positive or negative. In Kaplan–Meier analysis, they showed a trend towards developing more VE ( P = 0.06). Conclusion: IgG anti-DI antibodies were present in early serum samples from 29% of patients and were more common than IgG aCL or anti-β2GPI. There was some evidence suggesting that double or triple-ELISA-positivity for these antibodies identified a group with worse outcomes.